2017
DOI: 10.1093/jrr/rrx045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1950 MHz radiofrequency electromagnetic fields on Aβ processing in human neuroblastoma and mouse hippocampal neuronal cells

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease leading to progressive loss of memory and other cognitive functions. One of the well-known pathological markers of AD is the accumulation of amyloid-beta protein (Aβ), and its plaques, in the brain. Recent studies using Tg-5XFAD mice as a model of AD have reported that exposure to radiofrequency electromagnetic fields (RF-EMF) from cellular phones reduced Aβ plaques in the brain and showed beneficial effects on AD. In this study, we examined whether expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Oligomers and fibers have been shown to be neurotoxic, forming through the aggregation of Aβ monomers ( Söderberg et al, 2022 ), Aβ monomers include Aβ42 and Aβ40 monomers, Aβ42 and Aβ40 monomers are produced by anomalous cutting the amyloid precursor protein (APP) ( Jiang et al, 2014 ). Intracellular APP forms a sAPPβ fragment and a C-terminal fragment (C99), which are cleaved by ß -secretase (BACE1); the C99 peptide is further secreted by γ-secretase (PS1) to secrete Aβ monomers into extracellular space ( Park et al, 2018 ), abnormal aggregation in extracellular and intercellular space to then occurs to form Aβ oligomers and Aβ fibrous filaments ( Hong et al, 2015 ). Aβ42 is more neurotoxic than Aβ40 ( Tiwari et al, 2019 ), and we focused on Aβ42 monomers.…”
Section: Discussionmentioning
confidence: 99%
“…Oligomers and fibers have been shown to be neurotoxic, forming through the aggregation of Aβ monomers ( Söderberg et al, 2022 ), Aβ monomers include Aβ42 and Aβ40 monomers, Aβ42 and Aβ40 monomers are produced by anomalous cutting the amyloid precursor protein (APP) ( Jiang et al, 2014 ). Intracellular APP forms a sAPPβ fragment and a C-terminal fragment (C99), which are cleaved by ß -secretase (BACE1); the C99 peptide is further secreted by γ-secretase (PS1) to secrete Aβ monomers into extracellular space ( Park et al, 2018 ), abnormal aggregation in extracellular and intercellular space to then occurs to form Aβ oligomers and Aβ fibrous filaments ( Hong et al, 2015 ). Aβ42 is more neurotoxic than Aβ40 ( Tiwari et al, 2019 ), and we focused on Aβ42 monomers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on PTS irradiated (1950 MHz) neuroblastoma cells has suggested that RF-EMF exposure may not have a significant physiological effect on Aβ processing of neural cells in the short term [18], whereas our own work using also SY5Y cell line revealed that EMF exposure produces alterations on APP processing and cellular topology [19]. Interestingly, in a recent report [20] it has been shown that specific ranges of electromagnetic field parameters produce peptide conformations unfavourable for amyloid fibrils formation, a phenomenon that can be exploited in treatment and prevention of amyloid diseases Concerning Parkinson's disease (PD) it is considered the second major, progressive, neurodegenerative disorder that affects 1% of the over 60 population in industrialized countries [21].…”
Section: Introductionmentioning
confidence: 97%
“…Several scientific studies evaluate the possible effects of prolonged exposure to microwaves at the epidemiological level (4)(5)(6)(7)(8)(9)(10)(11) and in vitro or in vivo models (12)(13)(14)(15)(16)(17)(18)(19). However, the use of different methodologies in radiation measurement processes and different configurations of exposure equipment, such as frequency, radiation power density, and exposure time; do not allow adequate comparison of results, which makes it difficult to draw conclusions.…”
Section: Introductionmentioning
confidence: 99%